Non-Destructive Method for Estimating Log Volume for Melia Azedarach L. Trees in Erbil-Iraqi Kurdistan Region - Amin, Talat M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2014)
The accuracy of four traditional formulas (Smalian, Huber, Bruce and Newton) to calculate log volumes was compared and tested against volumes determined by the water-displacement technique (xylometer). 150 standing trees were measured in a Sami Abd-Alrahman Plantation Park in Erbil governorate on 1 May, 2012. The accuracy of these four procedures was analyzed considering merchantable outside bark volumes of logs of large, mid-and small diameter. The results showed that Newton’s formula was superior for all volumes and log lengths considered. Thus, Newton’s formula could be used in the majority of circumstances for log lengths of Melia azedarach trees. Applying the Newton formula to the tree volumes, DBH and height presented the best fit regression equation which for use in predicting the log volume of Melia azedarach trees in Erbil Governorate.